2015 IFPRI audited financial statements - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
2015 was a milestone year for the International Food Policy Research Institute (IFPRI) as it marked 40 years of influential research, communication, partnerships, and capacity strengthening in food policy. IFPRI's anniversary celebration on November 18 included a wide array of partners, both past and present, who have helped IFPRI fulfill its mission across the decades. Also toward the end of the year, IFPRI launched Compact2025, IFPRI's bold new initiative for ending hunger and under-nutrition by 2025. Compact2025 employs three strategic approaches: engaging countries in accelerating progress, with an initial focus on Bangladesh, Ethiopia, Malawi, and Rwanda; creating a knowledge and innovation hub; and supporting existing initiatives and partners. IFPRI continued to generate groundbreaking research throughout 2015, further contributing to IFPRI's reputation for high-quality work. For example, IFPRI helped shape global food policy priorities during the agenda-setting year in which the United Nations' General Assembly adopted 17 Sustainable Development Goals.